JARINGAN KOMUNIKASI PETANI DALAM PEMASARAN LIDAH BUAYA DI KALIMANTAN BARAT - Ellyta Ellyta (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
The theme of the research was communication network analysis of Aloe vera’s farmer in the central agribusiness area in Pontianak. The objectives of the research were: (1) to explain the diversity of communication network structure, (2) to explain the correlation between internal and external factors of communication and communication network, (3) to explain the correlation between communication network and farmers marketing behavior, (4) to explain the correlation between internal and external factors of communication and farmers marketing behavior. The respondents in the research was all of Aloe vera’s farmers, i,e., 67 person. The result of the research indicated that there were 7 respondents as stars, 4 as bridges, 2 respondents as liaison and 2 respondents as isolate. There were 7 cliques in the system in which 5 cliques take forms as radials or stars, 1 cliques as acircle form and 1 cliques takes form as all chanells. The research also indicated that there was correlation between internal and external factors and network communication; correlation between communication network and farmers marketing marketing behavior; correlation between internal and external factors and  farmers marketing behavior.